Prolonged pregnancy - Ludmir, A. (2015)
200 cases of prolonged pregnancy occurred between 1986-87 in the San Bartolome Hospital, compared with 200 normal cases taken at random is evaluated. The incidence of the problem was 2.76%. 70% of cases was controlled from the first half of pregnancy. The vast majority felt the first stirrings around week 20 and first auscultation fetoscope was made in 50% of cases, between weeks 18 and 21. In 80% of cases oligoamnios was observed and 50% sonographically senescence placental. In 60 cases nonreactive nonstress test, the stressful test was positive in 30% of patients; of which 50% with Bishop favorable were induced. Intercurrent problems of pre-eclamptic type was observed in 11.5% of cases. 73% completed his birth spontaneously, 15% was induced and 12% underwent cesarean section. Perinatal mortality was 30% compared to 25% occurred in the normal pregnancy group. Most deaths (60%) occurred in pre-eclamptic cases breakthrough. It points out that the evidence and auxiliary methods used in the hospital are satisfactory for the diagnosis of post-term pregnancy and to end the status of the newborn future.